Gyrinus aquiris LeConte 1868 - Majka, Christopher; Kenner, Rex (Zenodo, 2009)
Gyrinus aquiris LeConte, 1868 Gyrinus aquiris was reported from New Brunswick by Oygur and Wolfe (1991) and Roughley (1991) and from Nova Scotia by Campbell et al. (1987) (Fig. 8). In Nova Scotia it has only been found on Cape Breton Island (Fig. 2). Although Roughley (1991) reported it from Prince Edward Island, Majka (2008) removed it from the province’s faunal list since there are no voucher specimens or published records. Morrissette (1979) reported the species from ponds and lakes invaded by aquatic plants. Oygur and Wolfe (1991) reported 80% of specimens from lentic habitats. : Published as part of Majka, Christopher & Kenner, Rex, 2009, The Gyrinidae (Coleoptera) of the Maritime Provinces of Canada: new records, distribution, and faunal composition, pp. 355-372 in ZooKeys 22 (22) on page 362, DOI: 10.3897/zookeys.22.216, http://zenodo.org/record/576544 : {"references": ["LeConte JL (1868) The Gyrinidae of America, north of Mexico. Proceedings of the Academy of Natural Sciences of Philadelphia 20: 365 - 373.", "Oygur S, Wolfe GW (1991) Classification, distribution and phylogeny of North American (north of Mexico) species of Gyrinus Muller (Coleoptera: Gyrinidae). Bulletin of the American Museum of Natural History 207: 1 - 97.", "Roughley RE (1991) Family Gyrinidae: Whirligig Beetles. In: Bousquet Y (Ed) Checklist of Beetles of Canada and Alaska. Ottawa, Ontario: Agriculture Canada, publication 1861 / E: pp. 72 - 673. http: // www. canacoll. org / Coleo / Checklist / PDF files / GYRINIDAE. pdf [accessed 29 June 2009]", "Campbell JM, Bousquet Y, Bright DE, LeSage L, Smetana A (1987) Order Coleoptera. In: Lafontaine JD, Allyson S, Behan-Pelletier VM, Borkent A, Campbell JM, Hamilton KGA, Martin JEH, Masner L (Eds) The insects, spiders and mites of Cape Breton Highlands National Park. Biosystematics Research Centre, Agriculture Canada, Ottawa. 302 pp.", "Majka CG (2008) The aquatic Coleoptera of Prince Edward Island, Canada: new records and faunal composition. In: Majka CG, Klimaszewski J (Eds) Biodiversity, Biosystematics, and Ecology of Canadian Coleoptera. ZooKeys 2: 239 - 260. http: // pensoftonline. net / zookeys / index. php / journal / article / viewFile / 25 / 37 [accessed 29 June 2009]", "Morrissette R (1979) Les coleopteres Gyrinidae du Quebec. Cordulia, Supplement 8: 1 - 43."]}